Polyfunctional Properties of Cyanobacteria Isolated from the Saline Soils of Uzbekistan - G.Kh. , Kadirova; T.G. , Gulyamova; I.M. , Khalilov; Z.S. , Shakirov; O.I. , Jabbarovа; T.S. , Khusanov; S.B. , Sobirov (International Journal of Psychosocial Rehabilitation, 2020)
Salt tolerance of the local cyanobacterial strains of the genera Nostoc, Anabaena, Gloeothece, and Synechococcus was studied. The strains were subjected to growth and development at NaCl concentrations ranging from 100 to 500 mM. 200 mM NaCl was found not to affect the nitrogen-fixing activity of the cultures. Production of indole acetic acid by N. calcicola 25 at salinization (300 mM NaCl) with concentrations of tryptophan of 0.5 and 2.5 mg/ml was 26.6 and 48.6 mg/l, respectively. The polychlorinated biphenyls’ destructive activity in the samples of N. pruniforme 20 and A. variabilis 21 after 4 months was 66.78% and 73.28%, respectively.